The “Friends of Chile”: Pinochet’S Regime and Thatcher’S Great Britain (1979-1988) [Los “Amigos de Chile”: El Régimen de Pinochet y la Gran Bretaña de Thatcher (1979-1988)*] - Santoni, A (Universidad de Concepcion, 2022)
This paper, based on Chilean Ministry of Foreign Affairs sources, aims to provide an analysis of the Chilean military regime’s policy to face its difficult international position, focusing on the British case between 1979 and 1988. The Thatcher s government marked a substantial change in the relationship between the two countries: anticommunism and neoliberalism generated an ideological convergence that was enhanced by Chilean support for the United Kingdom during the Falklands war. However, this “friendship” was destined to find a limit in the pressure that the US and other European countries exerted on London, aimed at obtaining its collaboration with the democratization process in Chile. © 2022, Universidad de Concepcion. All rights reserved.